Metallothioneins 1 and 2 modulate inflammation and support remodeling in ischemic cardiomyopathy in mice - Duerr, Georg D.; Schmitz, Eva J.; Verfuerth, Luise; Keppel, Katharina; Peigney, Christine; Ghanem, Alexander; Welz, Armin; Dewald, Oliver; et al. (Mediators of Inflammation, 2016)
Aims. Repetitive brief ischemia and reperfusion (I/R) is associated with left ventricular dysfunction during development of ischemic cardiomyopathy. We investigated the role of zinc-donor proteins metallothionein MT1 and MT2 in a closed-chest murine model of I/R. Methods. Daily 15-minute LAD-occlusion was performed for 1, 3, and 7 days in SV129 (WT)- and MT1/2 knockout (M T-/-)-mice (n = 8-10/group). Hearts were examined with M-mode echocardiography and processed for histological and mRNA studies. Results. Expression of MT1/2 mRNA was transiently induced during repetitive I/R in WT-mice, accompanied by a transient inflammation, leading to interstitial fibrosis with left ventricular dysfunction without infarction. In contrast, MT-/- -hearts presented with enhanced apoptosis and small infarctions leading to impaired global and regional pump function. Molecular analysis revealed maladaptation of myosin heavy chain isoforms and antioxidative enzymes in MT1/2-/- -hearts. Despite their postponed chemokine induction we found a higher total neutrophil density and macrophage infiltration in small infarctions in M T-/- -hearts. Subsequently, higher expression of osteopontin 1 and tenascin C was associated with increased myofibroblast density resulting in predominately nonreversible fibrosis and adverse remodeling in MT1/2-/--hearts. Conclusion. Cardioprotective effects of MT1/2 seem to be exerted via modulation of contractile elements, antioxidative enzymes, inflammatory response, and myocardial remodeling.
CRIS-Team Scopus Importer:2022-05-03